The Mind After Midnight: Nocturnal Wakefulness, Behavioral Dysregulation, and Psychopathology - Tubbs, Andrew S.; Fernandez, Fabian-Xosé; Grandner, Michael A.; Perlis, Michael L.; Klerman, Elizabeth B. (Frontiers in Network Physiology, 2022)
Sufficient sleep with minimal interruption during the circadian/biological night supports daytime cognition and emotional regulation. Conversely, disrupted sleep involving significant nocturnal wakefulness leads to cognitive and behavioral dysregulation. Most studies to-date have examined how fragmented or insufficient sleep affect next-day functioning, but recent work highlights changes in cognition and behavior that occur when someone is awake during the night. This review summarizes the evidence for day-night alterations in maladaptive behaviors, including suicide, violent crime, and substance use, and examines how mood, reward processing, and executive function differ during nocturnal wakefulness. Based on this evidence, we propose the Mind after Midnight hypothesis in which attentional biases, negative affect, altered reward processing, and prefrontal disinhibition interact to promote behavioral dysregulation and psychiatric illness.